The association between previous induced abortion and in vitro fertilization outcomes: A retrospective cohort study in Hefei, China. (July 2021) - Zou, Linbing; Hong, Mingyun; Dai, Zhijun; Zhu, Jiansheng; Peng, Qingmei; Wang, Weiye
Abstract: Objectives: To assess the association between previous induced abortion and in vitro fertilization (IVF) outcomes among Chinese women. Study design: In this retrospective cohort study, a total of 1436 infertility patients treated with IVF for the first time in the reproductive centre of Anhui Province Maternity and Child Health Hospital from February 2014 to April 2018 were selected as the study population, and 95 (6.6 %) had a history of induced abortion. Data were assessed from the hospital electronic database and medical records in the reproductive centre. Results: In total, 818 women (57.0 %) achieved clinical pregnancy, and 501 (34.9 %) achieved live birth. After adjustments for a series of potential confounding factors, women with a history of induced abortion had a significantly decreased probability of clinical pregnancy per transfer (OR: 0.71, 95 % CI: 0.53, 0.95, p = 0.037) and live birth per pregnancy (OR: 0.52, 95 % CI: 0.30, 0.90, p = 0.021) and a higher risk of miscarriage per pregnancy (OR: 1.89, 95 % CI: 1.24, 2.88, p = 0.009) than those without. Because relevant information was unavailable, the impacts of different types of previous induced abortion were not assessed. Conclusions: Previous induced abortion may have an adverse effect on IVF outcomes among infertility patients.